2010
DOI: 10.1016/j.schres.2010.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intra-amygdala activity to positively valenced faces in adolescent schizophrenia offspring

Abstract: Studies suggest that the affective response is impaired in both schizophrenia and adolescent offspring of schizophrenia patients. Adolescent offspring of patients are developmentally vulnerable to impairments in several domains, including affective responding, yet the bases of these impairments and their relation to neuronal responses within the limbic system are poorly understood. The amygdala is the central region devoted to the processing of emotional valence and its sub-nuclei including the baso-lateral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 74 publications
2
37
0
2
Order By: Relevance
“…These findings extend this work by showing the RME task to be a useful and valid test for detecting impairment in social cognition independent of IQ and EF in children with FASD. Previous studies have found activation in the amygdala, the superior temporal gyrus and the posterior superior temporal sulcus, using RME or other affective processing tasks (Adams et al, 2009; Barbour et al, 2010; Baron-Cohen et al, 1999b). Hence, in future neuroimaging research one would expect alcohol-related deficits in brain regions related to affective processing in children with FASD.…”
Section: Discussionmentioning
confidence: 96%
“…These findings extend this work by showing the RME task to be a useful and valid test for detecting impairment in social cognition independent of IQ and EF in children with FASD. Previous studies have found activation in the amygdala, the superior temporal gyrus and the posterior superior temporal sulcus, using RME or other affective processing tasks (Adams et al, 2009; Barbour et al, 2010; Baron-Cohen et al, 1999b). Hence, in future neuroimaging research one would expect alcohol-related deficits in brain regions related to affective processing in children with FASD.…”
Section: Discussionmentioning
confidence: 96%
“…In previous facial affect fMRI studies patients with schizophrenia and their non-psychotic relatives showed limbic system hypoactivation similarities (Barbour et al, 2010;Habel et al, 2010). In one study, patients with schizophrenia and their healthy siblings reported similar reduced right hemisphere activation (de Achával et al, 2012).…”
Section: Introductionmentioning
confidence: 82%
“…SCZ-Off are highly vulnerable both to developmental deviations in bio-behavioral signals (Barbour et al, 2010; Diwadkar et al, 2001; Diwadkar et al, 2006), and most likely as a consequence of these deviations, to psychiatric disorders (Paus et al, 2008). Incidence rates of schizophrenia-related or not otherwise specified psychosis in offspring of schizophrenia patients range from 8 to 20%, that is up to twenty times higher than the incidence in the general population (Erlenmeyer-Kimling & Cornblatt, 1987).…”
Section: Discussionmentioning
confidence: 99%